Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 1 - Functions - 1.3 Inverse, Exponential, and Logarithmic Functions - 1.3 Exercises: 23

Answer

$a.$ $y=f^{-1}(x)=\dfrac{6-x}{4}$ $b.$ The relationships $f^{-1}(f(x))=f(f^{-1}(x))=x$ are verified.

Work Step by Step

$f(x)=6-4x$ $a.$ Substitute $f(x)$ by $y$: $y=6-4x$ Solve the equation for $x$. Begin by taking $4x$ to the left side and $y$ to the right side: $4x=6-y$ Take the $4$ to divide the right side: $x=\dfrac{6-y}{4}$ Interchange $x$ and $y$ and write the inverse in $y=f^{-1}(x)$ form: $y=f^{-1}(x)=\dfrac{6-x}{4}$ $b.$ Check the inverse found by evaluating $f(f^{-1}(x))$ and $f^{-1}(f(x))$: $f(f^{-1}(x))=6-4\Big(\dfrac{6-x}{4}\Big)=6-6+x=x$ $f^{-1}(f(x))=\dfrac{6-(6-4x)}{4}=\dfrac{6-6+4x}{4}=\dfrac{4x}{4}=x$ The relationships $f^{-1}(f(x))=f(f^{-1}(x))=x$ are verified.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.